Lychee seed extract improves growth performance and hepatic health in largemouth bass (Micropterus salmoides) fed high-fat diets: Novel insights from network pharmacology and in vivo validation - Zhenye Lin; Qi Li; Wenjie Chu; Shuling Bai; Shan Xie; Xiaotong Chen; Hao Chen; Zhipeng Zheng; Jiandong Zhu; Yongxin Liu; Yingying Yu; Tengfei Zhu (Aquaculture, 2027)

Phase evolution mechanism of selenium during hydrothermal conversion–atmospheric sulfuric acid leaching of copper anode slimes - Fang Shuling; Rao Shuai; Ma Zhiyuan; Liu Yejian; Tian Lei; Chen Lijie; Liu Zhiqiang; Zhang Liheng (Hydrometallurgy, 2026)

Ethylene-triggered membrane lipid catabolism mediated by the PpERF110/113-PpPLD2 regulatory module exacerbates chilling injury in peach fruit - Lufan Wang; Huijuan Zhou; Qiaocai Zhang; Shiying Zhang; Zhengwen Ye; Xiongwei Li; Mengyuan Chen; Ziyi Yuan; Xiangzhen Sun; Lichao Zhou; Shuling Shen; Xiaolin Zheng; et al. (Postharvest Biology and Technology, 2026)

Coupling of spectroscopy and nitrogen-oxygen isotopes unveils the mechanisms of dissolved organic matter and nitrate pollution in lakes within the agro-pastoral transition zone - Guodong Chai; Fang Yang; Haiqing Liao; Debin Jia; Weiying Feng; Chiamin Ho; Dongpin Liu; Shuling Chen; Jianguo Liu; Huibin Yu (Journal of Environmental Sciences, 2026)

Ameliorative effects of dietary curcuminoid supplementation on high-carbohydrate-diet-induced hepatic lipid metabolic disorders in largemouth bass (Micropterus salmoides) - Zhenye Lin; Zhipeng Zheng; Hongmian Mao; Wenjie Chu; Xiaotong Chen; Shan Xie; Shuling Bai; Qi Li; Hao Chen; Yongxin Liu; Jiandong Zhu; Tengfei Zhu; et al. (Aquaculture, 2026)

Methyl jasmonate alleviates chilling-induced browning in peach fruit through transcriptional suppression of PpLAC7 - Lufan Wang; Liang Zhou; Qiaocai Zhang; Huijuan Zhou; Lichao Zhou; Jiaxu Mao; Shiying Zhang; Mengyuan Chen; Ziyi Yuan; Xiangzhen Sun; Shuling Shen; Xiaolin Zheng; et al. (Postharvest Biology and Technology, 2026)

Europium-labeled polystyrene tracing reveals earthworm-mediated inhibition of root uptake and reduced phytotoxicity in lettuce - Nan Chang; Shiqi Bian; Qingliang Cui; Shuling Zhao; Tianyi Qiu; Li Chen; Tao Li; Peng-yang Wang; Roland Bol; Na Wang; Zhiqin Zhang; Fengyu Huang; et al. (Journal of Hazardous Materials, 2026)

Data-driven optimization of volatile fatty acid production from food waste in mono- and sludge-integrated co-fermentation systems - Fangnon Firmin Fangninou; Zhengguo Li; Zhan Yu; Guodong Yang; Dan Yu; Shuling Chen (Journal of Environmental Sciences, 2026)

Transcriptomic and metabolomic analysis reveals melatonin treatment in delaying postharvest yellowing in broccoli through ABA-pigment metabolism network - Yue Wang; Jianhui Cheng; Wenbo Lei; Shuling Shen; Yan Liu; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2026)

Effects and Mechanism of Lactobacillus gasseri CCFM1346 Combined with Rutin on Alleviating Hyperuricemia in Mice - Xin Tang; Shuling Zhang; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui (Probiotics and Antimicrobial Proteins, 2026)

Influences of environmental factors on the microbial community characteristics of bioaerosols in a cold region - Nami Lai; Shuozhen Tian; Silu Wang; Xiaoyan Wang; Ruihan Chen; Yuwei Liu; Huize Yang; Mengying Wang; Xiaoyu Cai; Wanying Yao; Shuling Li; Yue Xiao; et al. (Journal of Environmental Sciences, 2026)

Enhanced functionality and reduced allergenicity of silkworm pupae protein through Lactiplantibacillus plantarum fermentation - Jing Yang; Shuling Zhou; Yan Chen; Sutee Wangtueai; Jiajia Song (Food Chemistry, 2026)

Selection of adsorption and immobilization carriers under circulating flow conditions for enhanced performance and metabolic characteristics of Acidithiobacillus ferrooxidans - Fangzheng Zhou; Guanghui Chen; Yanyan Wang; Deshuang Yu; Yifan Zhu; Renjie Lu; Shufang Li; Shuling Xiao; Yingying Dong (Bioresource Technology, 2026)

AcERF61 transcription factor mediates ethylene-induced kiwifruit softening through directly regulating cell wall degradation genes - Lufan Wang; Jiaxu Mao; Shiying Zhang; Huijuan Zhou; Libin Wang; Liang Zhou; Mengyuan Chen; Ziyi Yuan; Xiangzhen Sun; Shuling Shen; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2026)

Endoscopic prediction model for detecting advanced rectal polyps after ileorectal anastomosis in familial adenomatous polyposis: a dual-center retrospective study - Zhilin Liu; Xingjie Gao; Shuling Chen; Linfu Zheng; Binbin Xu; Gaozhen Deng; Wen Wang; Kun Lin; Chushu Li; Zhou Ye; Dazhou Li (Familial Cancer, 2026)

Herbacetin alleviates acute doxorubicin cardiotoxicity via regulating the ERK1/2-FOXO3a signaling pathway - Sijia Bian; Xinran Li; Peiyan Zhu; Zhiting Jiang; Chen Yan; Shuling Wei; Liqi Luo; Yuhua Zhu; Lan Luo (Human Cell, 2026)

Quasi-solid-state electrolytes enabling long-life flexible electrochromic energy storage smart windows - Li Liao; Shuling Xiang; Biyou Bao; Guanglong Xu; Chengli Zhang; Qiang Wang; Zhenhu Cao; Wentao Chen; Hongtao Cao; Hongliang Zhang (Chemical Engineering Journal, 2026)

Multiplex PCR and nanopore sequencing reveal the genetic stability of Hantaan virus in Xi’an, China - Hailong Chen; Peng Zhang; Xiaoyue Chu; Yangni Deng; Mengying Yu; Leile Zhang; Quanli Du; Yuewen Han; Yujie Yang; Zerun Xue; Shuling Li; Rui Wu; et al. (Archives of Virology, 2026)

Mechanisms of blue light-mediated inhibition of chlorophyll degradation in ‘Newhall’ sweet orange during postharvest - Hui Sun; Yuwei Zhou; Sijia Liu; Qianqian Yu; Mengyao Yin; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2026)

Electrochemical aptasensor based on Zr-MOF@Ag nanocomposite for the rapid detection of chloramphenicol in honey, milk and lake water - Zhaoyuan He; Chengxiang Fu; Shuling Meng; Jiaqi Luo; Jieke Qiu; Jianing Huang; Xiaoge Duan; Jiakang He; Jinzi Wang; Hailan Chen (Food Chemistry, 2026)

Mechanisms of water-rock interaction and its impact on swelling and crack behavior of argillaceous dolomite in tunnel uplift zones - Zihang Liu; Kang Huang; Shuling Huang; Xianfeng Liu; Fei Yu; Shanxiong Chen; Zhangjun Dai (Bulletin of Engineering Geology and the Environment, 2026)

Cross-kingdom synthetic microbial community alleviates Cd toxicity and inhibits its uptake in rice - Xiaozhen Zhu; Qi Sun; Peiyu Li; Qingxuan Lu; Shuling Zhao; Li Chen; Shaoyuan Zhang; Hansong Chen (Applied Soil Ecology, 2026)

Exogenous melatonin regulates hormone metabolism involved in delaying the ripening process in cherry tomato fruit during storage - Hang Zhang; Yue Wang; Jianhui Cheng; Wenbo Lei; Keyu Xu; Lilai Yin; Chen Huan; Shuling Shen; Lanying Yao; Xiaolin Zheng (Postharvest Biology and Technology, 2025)

Aldometanib mitigates LPS-induced lung fibroblasts injury through the activation of AMPK-mediated signaling pathways - Fangfang Shao; Jianlong Xie; Lili Liang; Shuling Chen; Rilin Zhang (Toxicon, 2025)

Exogenous melatonin activates BoNAC52-BoRBOHF module and antioxidant system involved in the delay in broccoli yellowing during postharvest - Yue Wang; Lufan Wang; Yuting Li; Wenbo Lei; Jianhui Cheng; Yuan Cheng; Shuling Shen; Lanying Yao; Lichao Zhou; Yan Liu; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2025)

Methyl jasmonate regulates the glycolytic pathway and the PpbZIP43-PpFAD2 module to enhance cold resistance in peach fruit - Lufan Wang; Yuxuan Wang; Jiaxu Mao; Huijuan Zhou; Libin Wang; Binger Dai; Liang Zhou; Shiying Zhang; Shuling Shen; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2025)

Coal Measure Gas System of the Middle Jurassic Xishanyao Formation, Southern Margin of the Junggar Basin, China - Aobo Zhang; Shida Chen; Dazhen Tang; Shu Tao; Shuling Tang; Yifan Pu; Taiyuan Zhang (Journal of Earth Science, 2025)

p-chlorophenylalanine treatment accelerates tomato fruit ripening through hormone synthesis and glycolytic pathway during storage - Keyu Xu; Ran Yan; Hang Zhang; Lilai Yin; Wenbo Lei; Jianhui Cheng; Chen Huan; Yan Liu; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2025)

1-MCP regulates taste development in cold-stored peach fruit through modulation of sugar, organic acid, and polyphenolic metabolism - Huijuan Zhou; Zhengwen Ye; Lufan Wang; Shiying Zhang; Ziyi Yuan; Mingshen Su; Xianan Zhang; Jihong Du; Xiongwei Li; Minghao Zhang; Yang Hu; Shuling Shen; et al. (Postharvest Biology and Technology, 2025)

Integration of machine learning and meta-analysis reveals the behaviors and mechanisms of antibiotic adsorption on microplastics - Shuangshuang Bi; Ruoying Wu; Xiang Liu; Peng Wei; Shuling Zhao; Xinru Ma; Enfeng Liu; Hongfeng Chen; Jinling Xu (Journal of Hazardous Materials, 2025)

Effects of high hydrostatic pressure processing on the physicochemical properties, functional characteristics, and antioxidant activity of silkworm pupae protein - Jing Yang; Shuling Zhou; Yan Chen; Jiawang Jin; Jiajia Song (Food Chemistry, 2025)

Application of edible insects to food products: A review on the functionality, bioactivity and digestibility of insect proteins under high-pressure/ultrasound processing - Jing Yang; Yan Chen; Linqing Zhang; Shuling Zhou; Linfeng You; Jiajia Song (Food Chemistry, 2025)

Transcriptomics analysis reveals the regulatory role of PsERF3 in anthocyanin biosynthesis of ‘Taoxingli’ plum fruit in response to MeSA treatment - Lichuan Lou; Xiaoli Hu; Jiao Cheng; Yuan Cheng; Mengyao Yin; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2025)

Overexpression of OsGASR1 promotes Al tolerance in rice - Shuling Cao; Liyun Peng; Jinyu Yu; Ziheng Li; Zhigang Wang; Dan Ma; Xiaoqian Sun; Huawei Zheng; Baolei Zhang; Xingxiang Chen; Zhufeng Chen; Jixing Xia (Plant Science, 2025)

Moisture-absorbing expansion and cracking characteristics of central Sichuan red-bed mudstone based on digital speckle correlation method - Kang Huang; Zhangjun Dai; Shuling Huang; Fei Yu; Shichang Li; Kaiwen Tong; Wei Zhang; Shanxiong Chen (Bulletin of Engineering Geology and the Environment, 2025)

Control efficiency and potential mechanisms of chlorogenic acid against postharvest gray mold caused by Botrytis cinerea on peach fruit - Binger Dai; Yuxuan Wang; Huijuan Zhou; Lufan Wang; Liang Zhou; Jiaxu Mao; Shiying Zhang; Shuling Shen; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2024)

Unveiling the impacts of microplastic pollution on soil health: A comprehensive review - Nan Chang; Li Chen; Na Wang; Qingliang Cui; Tianyi Qiu; Shuling Zhao; Haoran He; Yi Zeng; Wei Dai; Chengjiao Duan; Linchuan Fang (Science of The Total Environment, 2024)

Biochar enhances Cd mineralization through microbially induced carbonate precipitation as a soil remediation strategy for rice paddies - Dinghua Peng; Xianghan Chen; Shuling Zhang; Guoquan Zeng; Chaoqun Yan; Huanyan Luo; Huakang Liu; Heng Xu (Chemosphere, 2024)

Synergistic enhancement of plant growth and cadmium stress defense by Azospirillum brasilense and plant heme: Modulating the growth–defense relationship - Qingliang Cui; Jingzi Beiyuan; Yinglong Chen; Mengdi Li; Tianyi Qiu; Shuling Zhao; Xiaozhen Zhu; Hansong Chen; Linchuan Fang (Science of The Total Environment, 2024)

Exogenous melatonin delays yellowing in postharvest broccoli by regulation of ABA and carotenoid metabolite - Ran Yan; Mariama Kebbeh; Yuan Cheng; Yue Wang; Yuting Li; Maorun Fu; Yan Liu; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2024)

Inhibitiory mechanism of phloretin on xanthine oxidase and its synergistic effect with allopurinol and febuxostat - Jiaqi Wen; Shuling Chen; Le Deng; Xinru Chen; Xiaoyu Jiang; Xing Hu; Deming Gong; Guowen Zhang (Food Bioscience, 2024)

Gas content evaluation in deep coal seam with an improved method and its geological controls - Haiqi Li; Shida Chen; Dazhen Tang; Shuling Tang; Jiaosheng Yang (Frontiers of Earth Science, 2024)

Influence of Fe substitution on structural stability and hydrogen storage/compression performance: A theoretical and experimental study on TiCr1.5-Mn0.5Fe alloys - Wenbin Jiang; Shuling Chen; Hanhao Shen; Zhijie Cao; Changchun He; Xiaobao Yang; Liuzhang Ouyang (Chemical Engineering Journal, 2024)

Absorption, metabolism, bioactivity, and biotransformation of epigallocatechin gallate - Shuling Zhang; Bingyong Mao; Shumao Cui; Qiuxiang Zhang; Jianxin Zhao; Xin Tang; Wei Chen (Critical Reviews in Food Science and Nutrition, 2024)

Microplastic pollution promotes soil respiration: A global‐scale meta‐analysis - Shuling Zhao; Matthias C. Rillig; Haijian Bing; Qingliang Cui; Tianyi Qiu; Yongxing Cui; Josep Penuelas; Baiyan Liu; Shiqi Bian; Fazel Abdolahpur Monikh; Jing Chen; Linchuan Fang (Global Change Biology, 2024)
Microplastic (MP) pollution likely affects global soil carbon (C) dynamics, yet it remains uncertain how and to what extent MP influences soil respiration. Here, we report on a global meta‐analysis to determine the effects of MP pollution on the soil microbiome and CO 2 emission. We found that MP pollution significantly increased the contents of soil organic C (SOC) (21%) and dissolved organic C (DOC) (12%), the activity of fluorescein diacetate hydrolase (FDAse) (10%), and microbial biomass (17%), but led to a decrease in microbial diversity (3%). In particular, increases in soil C components and microbial biomass further promote CO 2 emission (25%) from soil, but with a much higher effect of MPs on these emissions than on soil C components and microbial biomass. The effect could be attributed to the opposite effects of MPs on microbial biomass vs. diversity, as soil MP accumulation recruited some functionally important bacteria and provided additional C substrates for specific heterotrophic microorganisms, while inhibiting the growth of autotrophic taxa (e.g., Chloroflexi , Cyanobacteria ). This study reveals that MP pollution can increase soil CO 2 emission by causing shifts in the soil microbiome. These results underscore the potential importance of plastic pollution for terrestrial C fluxes, and thus climate feedbacks.

Comparison of the osteogenic potential of fibroblasts from different sources - Jiaojiao Li; Liangliang Fu; Qian Lu; Shuling Guo; Si Chen; Ting Xia; Min Wang; Liangwen Chen; Yi Bai; Haibin Xia (Tissue and Cell, 2024)

A meta-analysis on crop growth and heavy metals accumulation with PGPB inoculation in contaminated soils - Xiaohan Bai; Roland Bol; Hansong Chen; Qingliang Cui; Tianyi Qiu; Shuling Zhao; Linchuan Fang (Journal of Hazardous Materials, 2024)

Isoliquiritigenin retards starch digestion by increasing resistant starch content and inhibiting the activities of α-amylase and α-glucosidase - Yushi Wei; Le Deng; Shuling Chen; Xing Hu; Guowen Zhang (Food Bioscience, 2024)

Hybrid self-centering braces with NiTi-SMA U-shaped and frequency-dependent viscoelastic dampers for structural and nonstructural damage control - Shuling Hu; Yuji Koetaka; Zhi-Peng Chen; Songye Zhu; M. Shahria Alam (Engineering Structures, 2024)

Genesis and accumulation mechanism of external gas in deep coal seams of the Baijiahai Uplift, Junggar Basin, China - Bin Zhang; Shu Tao; Bin Sun; Shuling Tang; Shida Chen; Yijie Wen; Jincheng Ye (International Journal of Coal Geology, 2024)

Construction and characterization of egg white protein-gallic acid-xanthan gum-based emulsion and oleogel - Yuzhong Yan; Shuling Chen; Le Deng; Yuxuan Duan; Zhaohua Huang; Deming Gong; Guowen Zhang (Food Hydrocolloids, 2024)

Meta-analysis of impacts of microplastics on plant heavy metal(loid) accumulation - Li Chen; Nan Chang; Tianyi Qiu; Na Wang; Qingliang Cui; Shuling Zhao; Fengyu Huang; Hansong Chen; Yi Zeng; Faqin Dong; Linchuan Fang (Environmental Pollution, 2024)

Interaction of microplastics with heavy metals in soil: Mechanisms, influencing factors and biological effects - Baiyan Liu; Shuling Zhao; Tianyi Qiu; Qingliang Cui; Yuyi Yang; Lili Li; Jing Chen; Min Huang; Ai Zhan; Linchuan Fang (Science of The Total Environment, 2024)

Transcriptomic analysis reveals the role of abscisic acid and ethylene in regulating starch-source biosynthesis associated with soft nose disorder in ‘Keitt’ mango fruit during postharvest - Yuan Cheng; Ying Wang; Lichuan Lou; Yuxuan Wang; Binger Dai; Yue Wang; Mariama Kebbeh; Chen Huan; Shuling Shen; Yan Liu; Xiaolin Zheng; Jeffrey K. Brecht (Postharvest Biology and Technology, 2024)

Assessment of Hydrodynamic Performance and Motion Suppression of Tension Leg Floating Platform Based on Tuned Liquid Multi-Column Damper - Fuyin Cui; Shuling Chen; Hongbin Hao; Changzhi Han; Ruidong Ni; Yueyue Zhuo (Journal of Marine Science and Engineering, 2024)
To address the unstable motion of a tension leg platform (TLP) for floating wind turbines in various sea conditions, an improved method of incorporating a tuned liquid multi-column damper (TLMCD) into the TLP foundation is proposed. In order to evaluate the control effect of TLMCD on the motion response of the floating foundation, a multiphase flow solver based on a viscous flow CFD method and overlapping grid technique is applied to model the coupled multi-body dynamics interaction problem involving liquid tanks, waves, and a spring mooring system. This method has been proven to accurately capture the high-frequency motions of the structure and account for complex viscous interferences affecting the geometric motions. Additionally, the volume of fluid (VOF) method and the first-order linear superposition method are used to model the focused wave, enabling a simulation of the effects of transient wave loads on the floating foundation. The results show that the tuned damping effect of TLMCD on the TLP is mainly in the pitch motion, with the maximum pitch amplitude control volume ratio of TLMCD reaching up to 86% and the maximum surge amplitude control volume ratio of TLMCD reaching up to 25.2% under the operating conditions. These findings highlight the potential for additional research on and implementation of TLMCD technology.

HNF4A as a potential target of PFOA and PFOS leading to hepatic steatosis: Integrated molecular docking, molecular dynamic and transcriptomic analyses - Rui Li; Zijing Zhang; Yuxin Xuan; Yulu Wang; Yuyan Zhong; Lingyin Zhang; Jinrui Zhang; Qian Chen; Shuling Yu; Jintao Yuan (Chemico-Biological Interactions, 2024)

Unraveling the molecular mechanisms of selenite reduction: transcriptomic analysis of Bacillus reveals the key role of sulfur assimilation - Ying Yang; Jiawei Jing; Shuling Fan; Zhuo Chen; Yuanyuan Qu (Biotechnology Letters, 2023)

PsbZIP1 and PsbZIP10 induce anthocyanin synthesis in plums (Prunus salicina cv. Taoxingli) via PsUFGT by methyl salicylate treatment during postharvest - Shuling Shen; Xiaoli Hu; Jiao Cheng; Lichuan Lou; Chen Huan; Xiaolin Zheng (Postharvest Biology and Technology, 2023)

Mechanistic insights into the detoxification of Cr(VI) and immobilization of Cr and C during the biotransformation of ferrihydrite-polygalacturonic acid-Cr coprecipitates - Hanyue Zhang; Yang Lu; Zhuozhi Ouyang; Wenjing Zhou; Xinyue Shen; Kun Gao; Shuling Chen; Yang Yang; Shiwen Hu; Chongxuan Liu (Journal of Hazardous Materials, 2023)

Temperature effects on microbial dissolved organic matter metabolisms: Linking size fractions, fluorescent compositions, and functional groups - Gang Tang; Binrui Li; Bowei Zhang; Shiwen Hu; Shuling Chen; Tong Liu; Qianqian Wang; Han Qiao; Xing Zheng (Science of The Total Environment, 2023)

Experimental investigation of thermodynamic and kinetic behaviors from water vapor adsorption on four typical clay minerals - Shuling Xiong; Manfei Chen; Hui Yu; Weihang Zhang; Qinhong Hu; Sheng He; Rui Yang (Gas Science and Engineering, 2023)

Synergistic interplay between Azospirillum brasilense and exogenous signaling molecule H2S promotes Cd stress resistance and growth in pak choi (Brassica chinensis L.) - Qingliang Cui; Dongdong Liu; Hansong Chen; Tianyi Qiu; Shuling Zhao; Chengjiao Duan; Yongxing Cui; Xiaozhen Zhu; Herong Chao; Yuhan Wang; Jie Wang; Linchuan Fang (Journal of Hazardous Materials, 2023)

Diverse viruses of marine archaea discovered using metagenomics - Yifan Zhou; Liang Zhou; Shuling Yan; Lanming Chen; Mart Krupovic; Yongjie Wang (Environmental Microbiology, 2023)
During the past decade, metagenomics became a method of choice for the discovery of novel viruses. However, host assignment for uncultured viruses remains challenging, especially for archaeal viruses, which are grossly undersampled compared to viruses of bacteria and eukaryotes. Here, we assessed the utility of CRISPR spacer targeting, tRNA gene matching and homology searches for viral signature proteins, such as major capsid proteins, for the assignment of archaeal hosts and validated these approaches on metaviromes from Yangshan Harbor (YSH). We report 35 new genomes of viruses which could be confidently assigned to hosts representing diverse lineages of marine archaea. We show that the archaeal YSH virome is highly diverse, with some viruses enriching the previously described virus groups, such as magroviruses of Marine Group II Archaea (Poseidoniales), and others representing novel groups of marine archaeal viruses. Metagenomic recruitment of Tara Oceans datasets on the YSH viral genomes demonstrated the presence of YSH Poseidoniales and Nitrososphaeria viruses in the global oceans, but also revealed the endemic YSH‐specific viral lineages. Furthermore, our results highlight the relationship between the soil and marine thaumarchaeal viruses. We propose three new families within the class Caudoviricetes for the classification of the five complete viral genomes predicted to replicate in marine Poseidoniales and Nitrososphaeria, two ecologically important and widespread archaeal groups. This study illustrates the utility of viral metagenomics in exploring the archaeal virome and provides new insights into the diversity, distribution and evolution of marine archaeal viruses.

Deletions in GSN gene associated with growth traits of four Chinese cattle breeds - Ao Qi; Wenxiu Ru; Yangkai Liu; Yu Yang; Jia Tang; Haiyan Yang; Shuling Yang; Kaixing Qu; Xianyong Lan; Chuzhao Lei; Bizhi Huang; Hong Chen (Molecular Genetics and Genomics, 2022)

Comparative Study on Added Resistance and Seakeeping Performance of X-Bow and Wave-Piercing Monohull in Regular Head Waves - Shuling Chen; Beilei Zou; Changzhi Han; Shiqiang Yan (Journal of Marine Science and Engineering, 2022)
Bow shape has been recognized as an important factor influencing the seakeeping performance and added resistance of ships. This paper presents a numerical comparative study on added resistance and seakeeping of model ships with ‘X-bow’ and a wave-piercing monohull in regular head waves using a computational fluid dynamics (CFD) software. Different wave heights, wavelengths and forward speeds are considered in the systematic investigation in order to characterize the added resistance and wave-induced motions, and to explore the local wave patterns. The results show a considerably different hydrodynamic characteristic by different bow shapes.

Characterization of Water Quality in Xiao Xingkai Lake: Implications for Trophic Status and Management - Shuling Yu; Xiaoyu Li; Bolong Wen; Guoshuang Chen; Anne Hartleyc; Ming Jiang; Xiujun Li (Chinese Geographical Science, 2021)

Brominated and phosphate flame retardants from interior and surface dust of personal computers: insights into sources for human dermal exposure - Lehuan Yu; Shuling Ru; Xiaobo Zheng; Shejun Chen; Huiying Guo; Guijuan Gao; Yuan Zeng; Yijie Tang; Bixian Mai (Environmental Science and Pollution Research, 2021)

Pyr-miR171f-targeted PyrSCL6 and PyrSCL22 genes regulate shoot growth by responding to IAA signaling in pear - Shuling Jiang; Qiuju Chen; Qiulei Zhang; Yi Zhang; Ningning Hao; Chunqing Ou; Fei Wang; Tianzhong Li (Tree Genetics & Genomes, 2018)

JAB1 accelerates odontogenic differentiation of dental pulp stem cells - Min Lian; Ye Zhang; Qijie Shen; Jing Xing; Xiaohui Lu; Dan Huang; Peipei Cao; Shuling Shen; Ke Zheng; Jinlong Zhang; Jie Chen; Yi Wang; et al. (Journal of Molecular Histology, 2016)

The Ac124 protein is not essential for the propagation of Autographa californica multiple nucleopolyhedrovirus, but it is a viral pathogenicity factor - Changyong Liang; Dandan Lan; Shuling Zhao; Lulu Liu; Yanan Xue; Yongli Zhang; Yun Wang; Xinwen Chen (Archives of Virology, 2015)

QSAR studies of antituberculosis drug using three-dimensional structure descriptors - Jianbo Tong; Yang Chen; Shuling Liu; Xiameng Xu (Medicinal Chemistry Research, 2013)

Comparison of male chimeric mice generated from microinjection of JM8.N4 embryonic stem cells into C57BL/6J and C57BL/6NTac blastocysts - Thomas J. Fielder; Charles S. Yi; Juliet Masumi; Katrina G. Waymire; Hsiao-Wen Chen; Shuling Wang; Kai-Xuan Shi; Douglas C. Wallace; Grant R. MacGregor (Transgenic Research, 2012)

Expression of glr gene encoding glutamate racemase in Bacillus licheniformis WX-02 and its regulatory effects on synthesis of poly-γ-glutamic acid - Feng Jiang; Gaofu Qi; Zhixia Ji; Shuling Zhang; Jun Liu; Xin Ma; Shouwen Chen (Biotechnology Letters, 2011)

A method for gravity anomaly separation based on preferential continuation and its application - Xiaohong Meng; Lianghui Guo; Zhaoxi Chen; Shuling Li; Lei Shi (Applied Geophysics, 2009)

Patterns of variation of the major histocompatibility complex class IIB loci in Chinese goose (Anser Cygnoides) - Xu Zhou; Chunjin Li; Kangle Yi; Hongyan Liang; Lu Chen; Yanling Sun; Shuling Niu; Wei Wu (Immunogenetics, 2009)

Oct4 is expressed in Nestin-positive cells as a marker for pancreatic endocrine progenitor - Hong Wang; Shuling Wang; Jiang Hu; Yaxian Kong; Shen Chen; Lingsong Li; Liying Li (Histochemistry and Cell Biology, 2009)